Analisis Kesalahan Siswa Kelas XI SMA Negeri 2 Indramayu dalam Menyelesaikan Soal Limit Fungsi Berdasarkan Self Regulated Learning - Ayu Fitriyah Ningsih; Nandang Nandang; Wiwit Damayanti Lestari (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2022)
This study aims to identify errors and describe the factors that cause students to make mistakes in solving function-limit questions based on self-regulated learning. This descriptive qualitative research was conducted at SMA Negeri 2 Indramayu 2021/2022. Subjects were identified in this study using the purposive sample technique. Data collection techniques used self-regulated learning questionnaires, function limit tests, and interviews. They were taken based on the subject of the questionnaire results. Based on the questionnaire results, it was divided into three categories: high, medium, and low. The results of this study revealed various kinds of errors, namely: factual errors that students did not write down symbol boundaries; operation error, incorrect operation of numbers; conceptual error, students do not understand limit rules; principle error, students determining the form of a group. Factors that cause errors are that students need help understanding the concept and are inappropriate when answering questions.